Exchange Rates and Employment Instability: Evidence from Matched CPS Data - Goldberg, Linda; Tracy, Joseph; Aaronson, Stephanie (American Economic Review, 1999)
Exchange Rates and Employment Instability: Evidence from Matched CPS Data by Linda Goldberg, Joseph Tracy and Stephanie Aaronson. Published in volume 89, issue 2, pages 204-210 of American Economic Review, May 1999